2022
DOI: 10.3390/toxics11010041
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Persistent Organic Pollutants between Adipose Tissue and Serum in Human Studies

Abstract: Blood is the most widely used matrix for biomonitoring of persistent organic pollutants (POPs). It is assumed that POPs are homogenously distributed within body lipids at steady state; however, the variability underlying the partitioning of POPs between fat compartments is poorly understood. Hence, the objective of this study was to review the state of the science about the relationships of POPs between adipose tissue and serum in humans. We conducted a narrative literature review of human observational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…plasma, which makes it a preferred matrix for long-term exposure assessment [26,27]. Furthermore, among patients after bariatric surgery, vAT was metabolically active and underwent substantial lipolysis [28].…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…plasma, which makes it a preferred matrix for long-term exposure assessment [26,27]. Furthermore, among patients after bariatric surgery, vAT was metabolically active and underwent substantial lipolysis [28].…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Most studies have focused on exposure levels in plasma or subcutaneous adipose tissue as opposed to directly in visceral adipose tissue (vAT) [22, 24, 25]. However, POPs have been shown to accumulate in vAT at higher levels than in serum or plasma, which makes it a preferred matrix for long‐term exposure assessment [26, 27]. Furthermore, among patients after bariatric surgery, vAT was metabolically active and underwent substantial lipolysis [28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that over 90% of human exposure to POPs released into the environment occurs through the consumption of contaminated food [ 39 ]. Given their lipophilic nature, POPs can be accumulated especially in the adipose tissue [ 40 , 41 , 42 , 43 ], and can be sequestrated in the liver [ 44 ], thus leading to metabolic dysfunctions.…”
Section: Nutrition Environmental Pollutants and Nafldmentioning
confidence: 99%
“…It has been estimated that over 90% of human exposure to POPs released into the environment occurs through the consumption of contaminated food [39]. Given their lipophilic nature, POPs can be accumulated especially in the adipose tissue [40][41][42][43], and can be sequestrated in the liver [44], thus leading to metabolic dysfunctions. Several POPs, including industrial chemicals such as PCBs, plasticizers including phthalates and bisphenol A (BPA), and agricultural pesticides act as EDCs by interfering with hormone signaling and endocrine functions [45,46].…”
Section: Persistent Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…However, other biological matrices may be of some interest as they may constitute a better proxy for systemic exposure. In their review, Moriceau et al (2023) [ 2 ] compared the serum/adipose tissue ratio for persistent organic pollutants (POPs) and sought to identify key factors that could explain why for some compounds the ratio differed from 1. All included studies reported high variability in the partition coefficients of POPs and the authors concluded that further research is still needed to better investigate the partitioning of POPs.…”
mentioning
confidence: 99%